MAPPING ABILITY ANALYSIS OF HIGH SCHOOL (HIGH SCHOOL) GEOGRAPHY SUBJECT TEACHERS IN WRITING SCIENTIFIC WORK IN KETAPANG REGENCY - Norsidi Norsidi (Universitas Sebelas Maret (UNS), 2019)
This study aims to determine the ability of high school (SMA) geography subject teachers in scientific writing in Ketapang Regency. This type of research is survey research which is included in the quantitative category. Therefore, this study uses a sample of one population and uses a questionnaire as an instrument of data collection. The subjects of this study were high school (E) / equivalent level geography subject teachers in Ketapang Regency, which numbered 18 people. Analyzing data is based on the calculation of the percentage of results of filling out questionnaires by respondents. Based on the results of research on the ability of high school level (Geography) subject teachers in scientific writing in Ketapang Regency with the following indicators: 1) the teacher's understanding in making scientific papers has an overall average of 2.5 which is categorized as good; 2) the routine activities that geography subject teachers have done in developing their competencies have an overall average of 2.5 categorized as good; 3) teacher constraints in making scientific papers have an average of 2.38 categorized as less.Teacher's Ability, Writing Scientific Work